Aristocratic Agency and Religious Transformation: The Role of Pajajaran Elites in the Islamization of Banten - saepudin didin; Zubair Zubair; Fahmi Irfani; Alfida Alfida (Buletin Al-Turas, 2026)
Purpose This study aimed to explain the role of the Pajajaran Kingdom's nobility in the Islamization process of Banten. It focuses on tracing how local elites contributed to the region’s emerging Islamic identity and participated in the socio-religious transformation that accompanied the early spread of Islam.  Method The research employed a qualitative, descriptive-historical approach. Primary sources — including manuscripts, chronicles, archival materials, and historical documents—were analyzed through textual examination and historical reconstruction to uncover the political, cultural, and religious dynamics linking Pajajaran nobles with key actors in Banten’s Islamization.  Results/findings The study finds that Pajajaran nobles played an active role in Islamization, not as marginal figures but as agents of transformation. Figures such as Syarif Hidayatullah, Maulana Hasanuddin, Ki Agus Jo, and Mas Jong used persuasive strategies grounded in Sufi values, facilitating broad acceptance of Islam. Their efforts consolidated Banten’s position as a prominent Islamic sultanate in the Nusantara between the sixteenth and eighteenth centuries.  Conclusion The findings reaffirmed that Islamization in Indonesia unfolded through peaceful and cultural means rather than religious hegemony. Future research is encouraged to investigate the contributions of other local actors within the wider Islamization networks of the archipelago.